2013
DOI: 10.1080/13557858.2012.708914
|View full text |Cite
|
Sign up to set email alerts
|

Developing culturally congruent weight maintenance programs for African American church members

Abstract: The results suggest that integrating faith themes into a weight loss maintenance program may increase its long-term impact on participants' health behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Consistent with our findings, Reicks et al [18] identified how women in the study drew on their relationship with God through praying for help to overcome emotional eating and using Biblical scriptures to understand eating behaviour, which then encouraged women to change their motives for eating. Similarly, the findings of a recent focus group study of participants who had previously participated in a church-based weight loss programme mirrored the findings of our study [19]. Seale et al [19] concluded that participants anchored themselves on key scriptures, for example 1 Corinthians 6:19, where the body is described as a temple of the Holy Spirit-this provided them with a conscious awareness to treat their bodies better, which in turn motivated them to maintain the behavioural changes learned on the interventions.…”
Section: Interpretation Of Findings and Consistency With Other Findingssupporting
confidence: 76%
See 2 more Smart Citations
“…Consistent with our findings, Reicks et al [18] identified how women in the study drew on their relationship with God through praying for help to overcome emotional eating and using Biblical scriptures to understand eating behaviour, which then encouraged women to change their motives for eating. Similarly, the findings of a recent focus group study of participants who had previously participated in a church-based weight loss programme mirrored the findings of our study [19]. Seale et al [19] concluded that participants anchored themselves on key scriptures, for example 1 Corinthians 6:19, where the body is described as a temple of the Holy Spirit-this provided them with a conscious awareness to treat their bodies better, which in turn motivated them to maintain the behavioural changes learned on the interventions.…”
Section: Interpretation Of Findings and Consistency With Other Findingssupporting
confidence: 76%
“…Similarly, the findings of a recent focus group study of participants who had previously participated in a church-based weight loss programme mirrored the findings of our study [19]. Seale et al [19] concluded that participants anchored themselves on key scriptures, for example 1 Corinthians 6:19, where the body is described as a temple of the Holy Spirit-this provided them with a conscious awareness to treat their bodies better, which in turn motivated them to maintain the behavioural changes learned on the interventions. Participants in our study also anchored themselves on specific scriptures including this one when navigating through their daily lives post-intervention.…”
Section: Interpretation Of Findings and Consistency With Other Findingssupporting
confidence: 76%
See 1 more Smart Citation
“…NGT facilitates balanced participation among participants (13) and permits qualitative data to be transformed into a structured rank list (14). This method has been previously used in studies to generate feedback to develop health promotion programs targeted to AAs (15,16). …”
Section: Methodsmentioning
confidence: 99%
“…Given the strong identification with religion as a social support mechanism, and its importance in the everyday lives of AAs, it follows that health interventions incorporating spiritual and cultural contextualization have been effective [10][11][12]. Health promotion interventions conducted in faith communities provide a promising opportunity to enhance emotional, physical and spiritual health.…”
Section: Introductionmentioning
confidence: 99%